Structured soil mixture for solving deformation issue in GeoBarrier System - Chua,Yuan Shen (2022)
The GeoBarrier System (GBS) is designed to improve the urban sustainability with the planting bags within it. The GeoBarrier System (GBS) is a man-made 3-layered cover system comprising an exposed vegetative layer combined with hidden 2-layered unsaturated covered system, which harnesses the distinct difference in unsaturated hydraulic properties between a non-cohesive fine-grained layer and a coarse-grained layer. Previous research works indicated that GBS could be used as an earth retaining structure and slope stabilization system against rainfall-induced slope failures. However, the differential settlement was observed along the approved soil mixture (ASM) geobag layers in the previous study. The objective of this project is to investigate the appropriate modification of ASM layers in order to reduce the deformation of planting GeoBags. The research works involved the mixing of ASM with different percentages of recycled concrete aggregate (RCA) (called structured soil mixture or SSM) to improve the modulus elasticity of ASM layer within the planting geobag. The scope of this study includes the laboratory experiments for saturated and unsaturated soil characterization, numerical analyses and loading tests. The results indicated that the soil mixture with a ratio of 50% ASM and 50% coarse RCA can be used to provide improved resistance to deformation of GBS.